Train your brain puzzle book Level 2, For advanced puzzlers - Biritish Mensa (London Carlton Kids, 2014)
If you love to solve puzzles, this is the book for you, it's packed with brain-scrambling challenges created by mensa, the high IQ society, to train your brain and be great fun, too
Games & Recreations
1 23
Keywords: Mathematical recreations -- Children's nonfiction; Mathematical recreations; Puzzles -- Children's nonfiction